2006
DOI: 10.1111/j.1540-8183.2006.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Implantation of Aortic Valve Prosthesis in Patients with Calcific Aortic Stenosis: Technical Advances, Clinical Results and Future Strategies

Abstract: To date, one third of patients with symptomatic aortic stenosis are not operated on because of advanced age, depressed left ventricular function, or comorbidities. Whereas balloon aortic valvuloplasty can be used as a palliative treatment in this population, the hemodynamic and clinical benefits of the procedure are only temporary. With the goal of offering to this subset of patients a nonsurgical therapeutic option with improved results and longer term positive outcomes, we developed a percutaneous implantabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Transcatheter aortic valve implantation (TAVI) is becoming a viable alternative to open heart surgery in high-risk patients with aortic stenosis [1][2][3][4][5][6]. Despite long-term data on TAVI outcomes remain limited, the procedure is associated to early functional class improvement, with an overall success rate ranging from 74% to 100% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) is becoming a viable alternative to open heart surgery in high-risk patients with aortic stenosis [1][2][3][4][5][6]. Despite long-term data on TAVI outcomes remain limited, the procedure is associated to early functional class improvement, with an overall success rate ranging from 74% to 100% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In a report of the initial 36, primarily transvenous, patients from France, valve implantation was successful in 75% (17). Although problematic, this early transvenous experience did document the feasibility of the procedure and the potential for durable benefit.…”
Section: Early Outcomesmentioning
confidence: 94%
“…Initial experience with transcatheter valves suggested that paravalvular regurgitation was often severe (2,17,24). With various modifications of the procedure, such severe leaks are infrequent.…”
Section: Valve Functionmentioning
confidence: 98%
“…The first percutaneous aortic valve replacement was performed in France in 2002 [23]. Early results of this procedure are encouraging [24].…”
Section: Percutaneous Valve Repair and Replacementmentioning
confidence: 98%